A Small Mammal Survey Within The Planted Forest Zone, Bintulu, Sarawak - Roslina, Ragai; Andrew Alek, Tuen (2006)
A small mammal survey was conducted in areas of planted forest and secondary growth forest in the Forest Department Sarawak's Planted Forest Zone (PFZ) in the Bintulu Division. Two comprehensive small mammal trapping surveys were conducted within the period 4 July until 29 July 2006 in order to study the small mammal assemblages in acacia plantation blocks and forest remnants of the PFZ. The two sites were Samarakan Planted Forest Zone (SPFZ) and Sg. Mina Wildlife Corridor (SMWC). For both sites the traps were paired within acacia plantings and in adjacent natural secondary forest. From a total effort of 1400 trap-nights, 13 species of small mammals comprising 33 individuals from the family Tupaiidae (4 species), Sciuridae (3 species) and Muridae (6 species) were captured, giving an overall capture rate of 2.3%. Ten species were trapped within the acacia blocks and six species in secondary forest (lowland forest and riparian forest) within the PFZ. This preliminary result suggests that species richness was not influenced by forest types (acacia blocks versus forest remnants) but rather by location of the sampling plot within the PFZ. When different acacia blocks were compared, it was found that more species of small mammals were recorded in older acacia compared to younger acacia blocks, e.g. eight versus two species. Between the two forest remnants, riparian forest of SMWC was the poorest while the lowland forest remnant of Samarakan was relatively rich in small mammals. In comparison with other plantations, e.g., Sabah Softwoods and Bukit Tarek Plantation Forest, the number of species was higher even though the number of individuals was much lower. The underlying ecological causes for the pattern of small mammal distributions in the PFZ remain unclear. Further studies within other areas of PFZ are planned in order to better understand the patterns seen so far.